KEMUNGKINAN ELABORASI: KUALITAS SEBAGAI PESAN DALAM MEMPENGARUHI KEPUASAN DAN MINAT BERKUNJUNG KEMBALI - Alhasbi, Faruq; Amri, Saiful (Universitas Teuku Umar, 2020)
The tourism trend was change, marked by an increased in the exploration of cultural and historical tourism. The government through development program also support this phenomenon since 2014, with aim to increase the income through tourism sector. However, museum as cultural destinations have inverted trend. Quality as a message play important role to attract tourist. This research uses elaboration likelihood perspective to examine how quality as a message affects revisit intention. The result of quantitative process using SmartPLS showed that the effect of quality on tourist satisfaction is higher than quality on revisit intentions and the indirect effect of quality on revisit intention through tourist satisfaction is stronger than direct effect. It described that elaboration using central route is more effective to generating intention to travel back and intention to recommend. These results recommend that managers should improve some existing facilities and provide several supporting facilities or new facilities to increase visitor satisfaction. The elaboration by visitors proves that the use of the central route is more effective for museum marketing.